Nutritional Wizard - Vootla, Nikitha (Kansas State University, 2017)
It is well recognized that staying fit and healthy is a significant public problem now days and engaging in moderate levels of physical activity and having healthy food is associated with positive outcomes. Many dietary applications are being used at present times, but they don’t include physical activity in their assessment and even if they do so they require user to manually enter the data which gives room for unintentional mistakes. Nutritional wizard is a dietary and nutritional coach that works synchronously with Fitbit data to achieve this. This application analyses the food intake of an individual and automatically inspects this with his physical activity recorded through the Fitbit to give a cover on his health and fitness. The application has four main parts, input food, analysis, profile, and recipes. In input food part, user gives all the details of the food he had on that day and nutritional wizard gives the person’s calorie intake, steps he made on that day, calories spent, excess calories stored, steps he has to still make on that day. Analysis part of the application gives graphical representations of daily calorie intake in a specific time frame given by user. Profile has user’s height and weight based on which BMI of user is calculated and is represented in a Gantt chart showing if he is in low, good or high BMI. Last Recipes module has few recipes categorized into different selections low carb, low fat, and low protein which user can use to decrease his calorie intake. The completely developed app can be used by any user maintaining a fit bit account to provide good nutritional benefits.
Keywords: Nutritional coach; Dietary; Works synchronously; Fitbit data; Fit and healthy body; Daily calorie intake; BMI